Penerapan Model PBL dengan Pendekatan Saintifik dalam Pembelajaran Rasio untuk Meningkatkan Hasil Belajar - Noor Laily Anggraini; Sunarno Sunarno (Lembaga Bale Literasi, 2026)
This study aims to improve the learning outcomes of sixth-grade students on the topic of ratio equivalence through the implementation of the Problem-Based Learning (PBL) model with a scientific approach. The research employed a Classroom Action Research (CAR) design conducted in two cycles. Data were collected through student activity observations and learning outcome tests, covering the cognitive, affective, and psychomotor domains. The results showed a significant improvement in all three aspects. Student activity reached the